Ethnic -Zootechnic characterization and meat potential of Sus scrofa “creole Pig” in Latin America. - Linares, Virginia (2011)
The objective of this systematic scientific review was updated bibliographic information concerning the genetic, morphological, zootechnical and meat potential of creole pigs in Central and South America. It was found a population of 73 million Creoles pigs in Latin America, most under extensive, and semi extensive production systems. Since its European origin, adaptation to different ecosystems on the continent and the introduction of new breeds has led into a wide variety of creole pigs. Adaptation and introduction of breeds have led also in a rise of genetic variability of pigs benefiting the rusticity that involves a more efficient immune system. In the same way as omnivore the creole pig had a good adaptation to different diets, getting better advantage of fibrous and fatty food than commercial breeds. On the other hand, creole pigs showed an acceptable reproductive performance, distinguished by sexual precocity and high feasibility of weaning, nevertheless its growth was slow and lactation periods were long. Regarding to the quality of meat cuts , it has not been disadvantaged, if we take into account subjective criteria as well as tenderness and the nutritional value, characteristics that give higher economic value outstripping commercial pig meat.